Atendimento às vítimas de violência sexual do Hospital das Clínicas da Universidade Federal de Minas Gerais: quem são essas meninas e mulheres? - Raíza de Almeida Aguiar (2021)
Introduction: there were 66,123 rape victims in Brazil in 2019, one every eight minutes, 85.7% of them being female. Building evidence on how sexual assault occurs and what are the characteristics of the victims and the offenders can help in the development of tools to improve the access to and the quality of health services, as well as create initiatives to promote a culture of peace, violence prevention and recovery of the people involved. Objective: to analyze who are the girls and women victims of sexual violence attended at the outpatient clinic for sexual violence at the Hospital das Clínicas of the Universidade Federal de Minas Gerais (HC-UFMG). Methods: this is an observational and cross-sectional study, which involved 119 patients attended at the HC-UFMG sexual violence clinic from 11/01/2014 to 12/31/2020. Results: during the study interval, of the 119 victims of sexual violence treated, it was observed that most were adults (82.4%), brown (50.4%) and single (74.8%). 58% of them did not use contraceptive methods and were raped by a single aggressor (82.4%), with whom they had no previous relationship (59.7%). Using a bivariate distribution analysis, it was observed that the time to seek medical attention was proportionally bigger (greater than 5 days after the violence) among those who: were aged between 14 and 17 years (73.3%); were black (83 .3%); were divorced (74.8%); had a previous relationship with the aggressor (74.4%); were raped in events (76.9%); did not file a police report (86.2%) intervened with pregnancy (94.6%); had legal abortion authorized (96.6%). Discussion: in the population studied, most victims declared themselves brown (50%), followed by white (23%) and black (5%). There was a greater association between those victims who did not file a police report with those whose skin color was brown, regardless of whether or not they had suffered other aggressions. According to the correspondence analysis, victims aged 18 or over were associated with those who became pregnant when the interval in seeking care was late (more than 5 days), as well as with those who did not get pregnant when the interval was acute (up to 5 days). Victims who filed a police report, regardless of having suffered other aggressions or not, were more associated with victims whose skin color was white. In addition, there was a greater association between those victims who did not experience pregnancy and used emergency contraception with an interval time until the first visit of less than 1 day and between 1 and 7 days. Victims whose time until the first visit was greater than 7 days were associated with not using emergency contraception, regardless of whether it was a pregnancy or not, being stronger with victims who became pregnant. Final considerations: further studies are needed, using a methodology that includes other variables associated with the epidemiological profile of victims and aggressors for a better understanding of the users of this specialized service at the HC-UFMG.